Ketimpangan dan Autokorelasi Spasial Pertumbuhan Ekonomi Provinsi di Pulau Jawa dan Pulau Sumatera - Lies Maria Hamzah; Nuri Resti Chayyani (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2020)
This study aims to analyze inequality and spatial autocorrelation of provincial economic growth on the islands of Sumatra and Java. The study period starts from 2010 to 2015, which involves ten provinces on the island of Sumatra and six regions on the island of Java. This study uses the Williamson Index and Moran Index methods. The results of this study indicate that there are differences in income inequality. Java Island has a higher bias than Sumatra Island. The top income variation in Java is caused by high development in one of the provinces in Java while in Sumatra due to geographical and natural resource factors. Besides, the Moran Index shows that there is no spatial linkage of per capita GRDP between provinces in Sumatra and Java.